Both Low and Upper Normal Levels of 25-Hydroxy Vitamin D Relates to Risk Factors of Metabolic Syndrome and Cardiovascular Diseases - Masoumeh Akhlaghi; Majid Kamali; Farideh Dastsouz (Shiraz University of Medical Sciences, 2016)
Background: Vitamin D deficiency is implicated in a wide range of pathological situations including cardiovascular diseases. This study aimed to investigate the association between serum 25-hydroxy vitamin D (25(OH)D) and risk factors of metabolic syndrome and cardiovascular diseases. Methods: The cross-sectional study was conducted on 169 adults (88 males, 81 females) aged 19-52 years living in Shiraz, Iran. Anthropometric characteristics and blood pressure were measured using standard methods. Blood samples were collected in fasting state for determination of blood glucose, lipids, and 25(OH)D. Data were analyzed with one-way analysis of variance and linear regression using SPSS software. Results: Serum 25(OH)D concentrations were considerably higher in males. One third of females had vitamin D deficiency (25(OH)D <10 ng/ml) while one third of males exhibited 25(OH)D levels >50 ng/ml. In males, systolic and diastolic blood pressure, triglycerides, and metabolic syndrome score increased and high-density lipoprotein (HDL) cholesterol decreased across tertiles of serum 25(OH)D. On the contrary, in females body mass index (BMI) and metabolic syndrome score decreased and HDL cholesterol increased across tertiles of 25(OH)D. Linear regression, after controlling for confounding factors, showed that diastolic blood pressure (B=0.07; 95% CI: 0.02, 0.11; P=0.006), triglycerides (B=0.54; 95% CI: 0.22, 0.85; P=0.001), and metabolic syndrome score (B=0.01; 95% CI: 0.001, 0.01; P=0.02) positively and HDL cholesterol (B=-0.05; 95% CI: -0.09, -0.01; P=0.02) inversely associated with tertiles of 25(OH) D concentrations in males. In contrast, BMI (B=-0.06; 95% CI: -0.11, -0.02; P=0.01), waist circumference (B= -0.12; 95% CI:- 0.23, -0.01; p=0.04), and metabolic syndrome score (B=-0.02; 95% CI:-0.03, -0.01; P=0.01) were inversely and HDL-C (B=0.16; 95% CI: 0.02, 0.31; P=0.02) positively associated with 25(OH) D tertiles in females. Conclusion: The results suggest that both low and upper normal levels of 25(OH)D are associated with increased risk of cardiovascular diseases and metabolic syndrome